Study on Ka-band sheet-beam, three-slot-staggered-ladder coupled-cavity traveling-wave tube in a small tunable periodic cusped magnet. Issue 17 (22nd November 2017) - Liu, Hongwei; Wang, Zhanliang; Gong, Yubin; Wei, Yanyu; Duan, Zhaoyun; Gong, Huarong; Feng, Jinjun
Abstract: A Ka-band sheet electron beam (SEB) traveling-wave tube (TWT) based on three-slot staggered-ladder (TSTL) coupled-cavity slow-wave structure (CC-SWS) is proposed. The high-frequency characteristics of TSTL SWS were analyzed in detail. A well-matched input/output coupling system that solves the problem of energy coupling between the SWS and the external circuit was designed. A new method of loading the distributed attenuator for TSTL SWS was investigated for suppressing backward wave oscillation effectively. In addition, a SEB gun which can produce the SEB conveniently was optimized. A small tunable periodic cusped magnet (STPCM) system was designed to focus the low voltage, high-current SEB, which decreases the whole dimension of the TWT sufficiently. Moreover, the special STPCM system is predicted to exhibit 100% beam transmission efficiency. Finally, the beam-wave interaction was studied. The results obtained by CST simulation show that the SEB TWT can produce output power over 5 kW within the bandwidth ranging from 31.5 to 35.5 GHz, and the maximum output power is 10.15 kW at 33 GHz, corresponding electron efficiency of 10.36%. The fabrication of the device is under way.